2011
DOI: 10.1111/j.1365-2966.2011.19628.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper limits on the observational effects of nuclear pasta in neutron stars

Abstract: The effects of the existence of exotic nuclear shapes at the bottom of the neutron star inner crust – nuclear ‘pasta’– on observational phenomena are estimated by comparing the limiting cases that those phases have a vanishing shear modulus and that they have the shear modulus of a crystalline solid. We estimate the effect on torsional crustal vibrations and on the maximum quadrupole ellipticity sustainable by the crust. The crust composition and transition densities are calculated consistently with the global… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
130
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(136 citation statements)
references
References 68 publications
5
130
1
Order By: Relevance
“…We shall apply systematically and consistently generated sequences of crust and core EOSs together with the relevant crust compositions to calculate the relevant moments of inertia including that of the free crustal neutrons explicitly. The consistent modeling of crust and core properties when exploring the dependence of neutron star observables has been presented before (Gearheart et al 2011;Wen et al 2012), and here extends to modeling the crust thickness, density of superfluid neutrons throughout the crust, core EOS and core proton fraction using the same underlying nuclear matter EOSs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We shall apply systematically and consistently generated sequences of crust and core EOSs together with the relevant crust compositions to calculate the relevant moments of inertia including that of the free crustal neutrons explicitly. The consistent modeling of crust and core properties when exploring the dependence of neutron star observables has been presented before (Gearheart et al 2011;Wen et al 2012), and here extends to modeling the crust thickness, density of superfluid neutrons throughout the crust, core EOS and core proton fraction using the same underlying nuclear matter EOSs.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear experimental probes (e.g. Li et al (2008);Tsang et al (2012)) give a conservative range L = 20 − 120 MeV, although some more recent results on the nuclear experimental side (Lattimer & Lim 2013), as well as tentative constraints from neutron star observation (Newton & Li 2009;Gearheart et al 2011;Wen et al 2012;Steiner & Gandolfi 2012) and from ab-initio pure neutron matter calculations (Gezerlis & Carlson 2010;Hebeler & Schwenk 2010;Gandolfi et al 2012) tend to favor the lower half of that range (although, for a counter-example, see e.g. Sotani et al (2012)).…”
Section: Introductionmentioning
confidence: 99%
“…[30,31]. In fact, the elasticity in such region is expected to be lower than that in the droplet region [61] …”
Section: Neutron Star Modelsmentioning
confidence: 99%
“…In order to explain these QPO frequencies theoretically, a lot of numerical attempts have been done not only by the shear oscillations in the crust of neutron stars but also by the magnetic oscillations [17,18,19,20,21,22,23,24,25,26,27]. In addition, ascribing the observed QPOs to shear oscillations in the crust of neutron stars, the possibilities are also pointed out to reveal the properties of inhomogeneous nuclear matter in the crust [28,29,30,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…This technique is known as asteroseismology. In fact, important properties of the NS physics such as nuclear symmetry energy in the crust have been constrained by observations of quasiperiodic oscillations in the magnetar giant flares [23][24][25][26][27][28][29]. It has been also suggested that the properties of a cold NS, such as the mass (M), radius (R), and the nuclear equation of state (EOS), could be constrained by the direct observations of GWs (e.g., [30][31][32][33][34][35][36]).…”
Section: Introductionmentioning
confidence: 99%